Convergence of variational iteration method for solving singular partial differential equations of fractional order - Elbeleze, Asma Ali; Kilicman, Adem; M. Taib, Bachok (Hindawi Publishing Corporation, 2014)
We are concerned here with singular partial differential equations of fractional order (FSPDEs). The variational iteration method (VIM) is applied to obtain approximate solutions of this type of equations. Convergence analysis of the VIM is discussed. This analysis is used to estimate the maximum absolute truncated error of the series solution. A comparison between the results of VIM solutions and exact solution is given. The fractional derivatives are described in Caputo sense.